KEUNIKAN METODOLOGI TAFSIR AL-FARRA: MA’ANI AL-QUR’AN - Abdul Rohman; Barikli Mubaroka (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The Al-Farra Commentary is the oldest and first commentary in the history of exegesis, and its manuscript has survived to the present day. Its presence has been a source of inspiration for commentators who lived after him. From a content perspective, the commentary has its own uniqueness. The purpose of this writing is to reveal the uniqueness of the Al-Farra exegesis methodology entitled "ma’?n? al-Qur?n" (Meanings of the Quran). This writing is a type of literature research using descriptive analysis methods. The main source of the research is the Al-Farra commentary known as "ma’?n? al-Qur’?n," and supplementary sources include books, publications, and journal articles that are still relevant to the study's theme. The results of this research reveal that the Al-Farra commentary was written in response to a request from his colleagues. The method he used is the tahl?l? method, drawing references from the Quranic verses, Prophet's hadiths, the opinions of companions, and mostly incorporating the thoughts of linguistically adept scholars of his time and the preceding era. The predominant style is linguistic, particularly focusing on syntactic analysis, which is spread throughout every verse. The uniqueness of the Al-Farra commentary lies in its inclination to concentrate only on verses or sentences considered difficult from a grammatical perspective, providing more in-depth analysis of their linguistic aspects.